The status of prisoners between Islamic law and the Third Geneva Convention of 1949 - Khanfri, Meriam (Journal of Human Sciences, 2020)
The Islamic Fiqh and the 1949 Geneva Convention gave immense importance to prisoners in Geneva. Prisoner of war’s rights are: - The right to live in favorable accommodation than that which is also reserved for the troops of the detaining power. - The right to food, the clothes to dress properly. - The right to evacuate them to camps located far enough from the combat zone. - The right in all circumstances to respect for their honor. - They must grant them the necessary medical care free of charge. - Let them exercise their religious and spiritual activities. The Islamic Fiqh has given special rules to prisoners of war such as: manna, (exchange of prisoners), the edema contract, assassination and slavery. It was a matter of choosing between the rules for the good of their country